Current Challenges and Future Prospects of Green Construction in Malaysia - Sam, Wil Son; Primus, Audrey; Sentiveanu , Daniela; Puspitasari, Surya Dewi; Jannat, Md Abu Hanifa; Jayapadma, Jayapadma Mudalige Miyuru Uthpala; Illahi, Yuangga Rizky; Permana, Muhamad Diki; Maharjan, Amit Kumar; Maharjan, Rabin; Tongco, Jovale Vincent (Civil and Sustainable Urban Engineering, 2025)
Malaysia’s rapid urbanization, driven by a growing population and increasing industrial and infrastructural demands, significantly impacted the environment. The construction sector, a key contributor to economic growth, simultaneously became a major source of environmental degradation due to high resource consumption and waste generation. In response to these challenges, the integration of green materials and sustainable technologies emerged as a viable solution to minimize the negative environmental footprint of construction activities. This paper provides a comprehensive overview of the current state of green materials in Malaysia, including bamboo, organic waste, recycled concrete aggregate, and plastic waste, highlighting their benefits and limitations. Additionally, sustainable construction technologies such as solar energy, hydropower, biogas systems, green roofing, and rainwater harvesting are examined for their potential role in enhancing environmental sustainability. The study further evaluates existing government policies and regulations governing green construction in Malaysia, identifying key challenges such as ineffective waste management, regulatory enforcement gaps, and illegal dumping. Comparisons with international best practices, including those from Japan and Hong Kong, offer insights into potential improvements for Malaysia’s regulatory framework and implementation strategies. The paper also discusses the prospects of green materials and sustainable construction technologies, outlining potential solutions to enhance their adoption. By addressing both the challenges and opportunities within the sector, this review aims to contribute to the advancement of sustainable construction practices in Malaysia, ultimately fostering a eco-friendlier and more resilient built environment.